Allopregnanolone Association with Psychophysiological and Cognitive Functions during Acute Smoking Abstinence in Premenopausal Women - Allen, Alicia M. (Exp Clin Psychopharmacol, 2015)
Nicotine response may predict susceptibility to smoking relapse. Allopregnanolone, a neuroactive steroid metabolized from progesterone, has been shown to be associated with several symptoms of nicotine response. We sought to explore the association between allopregnanolone and response to nicotine during acute smoking abstinence in premenopausal women. Participants completed 2 nicotine response laboratory sessions, 1 in their follicular (low allopregnanolone) and 1 in their luteal (high allopregnanolone) menstrual phase, on the fourth day of biochemically confirmed smoking abstinence. During the laboratory sessions, participants self-administered a nicotine nasal spray and completed a timed series of cardiovascular, cognitive, and subjective assessments of response to nicotine. The relationships of allopregnanolone with baseline values and change scores of outcome measures were assessed via covariance pattern modeling. Study participants (n = 77) had a mean age of 29.9 (SD = 6.8) years and smoked 12.2 (4.9) cigarettes per day. Allopregnanolone concentration measured before nicotine administration was positively associated with systolic (β = 0.85, p = .04) and diastolic blood pressure (β = 1.19, p < .001); and self-report of physical symptoms (β = 0.58, p < .001), dizziness (β = 0.88, p < .01), jitteriness (β = 0.90, p = .04), and pleasantness (β = 2.05, p = .04). Allopregnanolone also had significant positive associations with change in cognition following nicotine nasal spray administration, specifically discriminability as a measure of attention (β = 1.15, p = .05) and response bias as a measure of impulsivity (β = 0.13, p = .02). These data suggest that allopregnanolone may be related to cardiovascular and subjective physical state during acute smoking abstinence, as well as cognitive response to nicotine.